Population Pharmacokinetics of Tigecycline for Critically Ill Patients Undergoing Continuous Renal Replacement Therapy - Song S; Liu J; Su W; Yu H; Feng B; Wu Y; Guo F; Yu Z (Drug Design, Development and Therapy, 2024)
Shuping Song,1,* Jieqiong Liu,2,3,* Wei Su,1 Haitao Yu,4 Binbin Feng,1 Yinshan Wu,1 Feng Guo,1 Zhenwei Yu2 1Intensive Care Unit, Sir Run Run Shaw Hospital, School of Medicine, Zhejiang University, Hangzhou, People’s Republic of China; 2Department of Pharmacy, Sir Run Run Shaw Hospital, School of Medicine, Zhejiang University, Hangzhou, People’s Republic of China; 3Department of Pharmacy, The 903rd Hospital of PLA Joint Logistic Support Force, Hangzhou, People’s Republic of China; 4Department of Clinical Laboratory, Sir Run Run Shaw Hospital, School of Medicine, Zhejiang University, Hangzhou, People’s Republic of China*These authors contributed equally to this workCorrespondence: Feng Guo; Zhenwei Yu, Email 3408003@zju.edu.cn; yzw_srrsh@zju.edu.cnBackground: Tigecycline is considered one of the last resorts for treating infections caused by multidrug-resistant bacteria. Continuous renal replacement therapy (CRRT) is widely used in critically ill patients, especially those with acute kidney injury or severe infections. However, pharmacokinetic data for tigecycline in patients receiving CRRT are limited.Methods: This was a single-center prospective clinical study with intensive sampling that included critically ill patients who received tigecycline and CRRT. A population pharmacokinetic (PPK) model was developed and evaluated by goodness-of-fit plots, bootstrap analysis, visual predictive checks, and numerical predictive checks. Pharmacokinetic/pharmacodynamic target attainment and cumulative fraction of response analyses were performed to explore the potential need for dose adjustments of tigecycline in CRRT.Results: In total, 21 patients with 167 concentrations were included. A two-compartment model adequately described the tigecycline concentration–time points, but no covariates were found to adequately explain the viability in the pharmacokinetic parameters of tigecycline. The typical values of CL, Q, V1 and V2 were 4.42 L/h, 34.8 L/h, 30.9 L and 98.7 L, respectively. For most infections, the standard regimen of 50 mg/12 h was deemed appropriate, expect for skin and soft skin tissue infections and community-acquired pneumonia caused by Acinetobacter baumannii and Klebsiella pneumoniae, which required a dosage regimen of 100 mg/12 h or higher.Conclusion: A tigecycline PPK model describing critically ill patients undergoing CRRT was successfully developed. The optimized dosage regimens for various infections are recommended.Keywords: tigecycline, population pharmacokinetics, critically ill, continuous renal replacement therapy